Penyusunan Laporan Keuangan Sederhana: UMKM Agro Jamur Lombok Kekeri - Siswanto, Topan; Nendy Pratama Agusfianto; Syaiful Amri; Satriawan (Valid Jurnal Pengabdian, 2025)
This community service activity was carried out at the Agro Jamur Lombok Kekeri MSMEs in Gunungsari District, West Lombok Regency, West Nusa Tenggara Province. Agro Jamur Lombok Kekeri MSMEs faces challenges in preparing financial reports due to a lack of basic understanding of financial record-keeping, weak awareness of the importance of good bookkeeping or financial management, and limited information on good financial governance. Based on these conditions, this activity was designed in the form of structured counseling and mentoring regarding simple financial record-keeping and report preparation by the financial standards applicable to MSMEs. This training/mentoring activity on preparing simple financial reports can increase the understanding of Agro Jamur Lombok Kekeri MSME actors about the importance of regularly recording every financial transaction based on valid evidence, as a basis for preparing daily and periodic financial reports by the financial standards applicable to MSMEs. This activity also successfully raised awareness of the importance of good, neat, and sustainable financial administration governance, as one of the important foundations for business sustainability. It is hoped that MSME actors will be disciplined in implementing good financial administration governance practices, which will have a positive impact on operational efficiency and better decision-making, so that the business can survive and even continue to grow.